The Fairy as Hero(ine) and Author: Representations of Female Power in Murat's "Le Turbot" - Melissa A. Hofmann (Wayne State University Press, 2015)
Henriette-Julie de Castelnau de Murat's "Le Turbot" (1699) is remarkable because its fairy Turbodine is both the tale's true hero and heroine and its author, a character both devel- oping the plot—her own and others'—and narrating it. Turbodine is the protagonist, and her heroic male power, integral to her authorship of the plot, is both highlighted and disguised by the text. Her power and its limitations are representative of the simultaneous influence and marginality of the woman writer of 1690s France.